ANALISIS PENGARUH HARGA, PRODUK, DAN KUALITAS LAYANAN TERHADAP KEPUASAN WISATAWAN DI TAMAN WISATA AIR WENDIT KABUPATEN MALANG - Stella Alvianna (Jurnal Pariwisata Pesona, 2017)
The purpose of research is to describe the price, product, and service quality to tourist satisfaction, to analyze the effect of pricing, product, and service quality, and to analyze between the price of the product, and the quality of service which the dominant influence on tourist satisfaction. The method used in this research is descriptive quantitative research methods survey technique which aims to clarify leverage causal relationship between variables through hypothesis testing verification. The data analysis in research used multiple linear regression followed by hypothesis testing. The results showed that the price, product, and quality of service simultaneously significant effect on satisfaction tourist in Taman Wisata Air Wendit Kabupaten Malang, this suggests that the price is comparable to rides that enjoyed by tourists, products that meet the desires and needs of tourists, and services presented optimally, then the tourists becomes obtaining an enjoyable experience so that tourists are interested to come and visit again. Price dominant influence on tourist satisfaction, the results showed that the price of the dominant influence, not a product. This is because the tourist assumes that the expenditure during a trip to Taman Wisata Air Wendit are in accordance with the benefits gained traveled by tourists